Growth response of coastal hibiscus (Hibiscus tiliaceus) seedlings to zeolite and glutamine under water stress - Ali Sabbar ALhasnawy; Kadum Mohammed Abdullah (Journal of Kerbala for Agricultural Sciences, 2025)
Water stress is one of the most prominent environmental factors negatively impacting plant growth and represents a significant challenge in areas with limited water resources. Therefore, this study aimed to explore the impact of water stress on the growth of coastal hibiscus seedlings and the role of zeolite and glutamine in mitigating it. A pot experiment was conducted during the spring season of 2024 according to a split-split-plot design with three replicates. The study included two levels of water stress (50% and 100% of field capacity), adding zeolite (0, 500, and 1000 g pot-1) and spraying with glutamine (0, 150, and 300 mg L-1). The results showed an apparent decrease in the studied traits (percentage increase in plant height, percentage increase in stem diameter, percentage increase in number of leaves, leaf area, percentage of dry matter) in plants stressed by (50% of field capacity) with decreased percentages of (6.33%, 2.80%, 7.10%, 2.68%, and 11.69%), respectively, compared to non-stressed plants. The results also demonstrated the effective role of the studied factors in mitigating the effects of water stress. Both zeolite and glutamine, either individually or in combination, contributed to reducing the resulting damage when applied to plants exposed to water stress at 50% of the field capacity. The results showed that growth rates were higher or similar to those recorded in non-stressed plants, which reinforces the role of these vital factors in improving the ability of plants to withstand water stress conditions.